A randomised crossover clinical trial of masticatory function in complete denture wearers with conventional and lingualised balanced occlusion - Pereira, Rodrigo de Paula; Rocha, Cibele Oliveira de Melo; Jabr, Camila Luiz; Oliveira, Lucas Portela; Arioli Filho, João Neudenir (Gerodontology, 2022)
Objectives The purposes of the present study were as follows: (1) to conduct a randomised crossover clinical trial to evaluate masticatory performance in wearers of conventional complete dentures in both arcs with conventional balanced occlusion (CBO) and lingualised balanced occlusion (LBO), using almonds as natural test food chewed for (a) 30 chewing cycles, (b) 40 chewing cycles and (c) until the subject felt ready to swallow and (2) to perform a randomised crossover clinical trial of oral health self‐perception through the Geriatric Oral Health Assessment Index (GOHAI) questionnaire. Background During rehabilitation with full dentures, achieving stability and retention is essential for masticatory performance. A factor that can act is the appropriate occlusal scheme to be used, although the literature is full of discussions as to the most suitable occlusal scheme to be used, being CBO and LBO the most used in complete dentures. Materials and Methods The clinical trial was conducted with 30 participants (14 males and 16 females; average age 65.8 years). A base of interchangeable posterior teeth in the lower dentures was used, thereby changing the occlusal schemes without needing to make another complete denture. The masticatory tests and GOHAI application were conducted in two sessions: first with each occlusal scheme, and second only after participants did not report discomfort with dentures. The analysis of variance for the mixed repeated‐measures test (ANOVA) was used to verify the results (α = 0.05). Results The results showed no difference in masticatory performance according to the occlusal scheme (P = .519). The masticatory performance increased with the number of cycles (P < .001) tested, regardless of the type of occlusion scheme, and oral health self‐perception was higher after the second masticatory evaluation session (P = .027). Conclusion The masticatory performance was similar between the two occlusal schemes, increasing according to the number of chewing cycles. The adaptive period is relevant, regardless of the occlusion scheme, because the time factor was decisive for the improvements noted in the oral health self‐perception of the participants (according to the GOHAI results).